Gambaran Histologi Lambung Dan Duodenum Mencit (Mus musculus L.) Jantan Yang Diberi Ekstrak Daun Kersen (Muntingia calabura L.) Setelah Diinduksi Monosodium Glutamat (MSG) - Ni Wayan Adya Puttry Purna Yogini; Ngurah Intan Wiratmini; Ni Gusti Ayu Manik Ermayanti (Prodi Magister Ilmu Biologi, Fakultas MIPA, Universitas Udayana, 2021)
The antioxidant contained in kersen (Muntingia calabura L.) leaves has been known to be able to prevent animal tissue damages. Monosodium glutamate (MSG) is a food additive substance associated with histological damage of duodenum as well as increases secretion of HCl in stomach if consumed in excess amount. This study aimed to investigate the histological features of stomach and duodenum of monosodium glutamate-induced mice (M. musculus) after treated with kersen leaves extract, as well as establishing its optimum dose. This study used a Completely Randomized Design, with 25 male mice assigned to 5 treatment groups: 2 control groups i.e. negative control (K-) given aquades and positive control (K+) given 0.7mg/body weight MSG; and 3 intervention groups which were given kersen leaves extract as much as 0.075 mg/g bw (P1), 0.15 mg/g bw (P2) and 0.3 mg/g bw (P3). Both kersen leaves extract and MSG was administered orally once daily for 28 days. The parameters observed were histological features of stomach features (erosion of villi and inflammatory cells infiltration) and duodenum (erosion of villi, necrosis, and inflammatory cell infiltration). The results showed that all parameters observed in the aforementioned organs were significantly different (P<0.05) in intervention groups (P1, P2, dan P3) compared with positive control (K+). It is concluded that administration of kersen leaves extract improved the damages of stomach, duodenum, and liver of MSG-induced mice, and was best achieved at the dose of 0.3 mg/g bw.